Review of Tell Me Why My Children Died: Rabies, Indigenous Knowledge and Communicative Justice, by Charles Briggs & Clara Martini-Briggs - Jerome, Jessica (European Review of Latin American and Caribbean Studies, 2017)
Tell Me Why My Children Died: Rabies, Indigenous Knowledge and Communicative Justice, by Charles Briggs & Clara Martini-Briggs. Duke University Press, 2016.